Emancipação pela educação encontros entre Piaget e Habermas - Nunes, Vinícius Bozzano (Editora Oficina Universitária, 2020)
This book is aimed at all people who believe in education and its emancipatory potential. Educators, school managers, students, researchers in the human sciences, education and, in particular, members of schools and educational experiences who are looking for alternatives, will find subsidies here so that they can reflect on the role of education in the face of contemporary challenges and on the emancipatory possibilities present in our civilization. The arguments are driven by the meeting of the main concepts of Jürgen Habermas' sociology and Jean Piaget's epistemology.